Miconazole Contributes to NRF2 Activation by Noncanonical P62-KEAP1 Pathway in Bladder Cancer Cells - Tsai TF; Chen PC; Lin YC; Chou KY; Chen HE; Ho CY; Lin JF; Hwang TIS (Dove Medical Press, 2020)
Te-Fu Tsai,1,2 Po-Chun Chen,3,4 Yi-Chia Lin,1,2 Kuang-Yu Chou,1,2 Hung-En Chen,1 Chao-Yen Ho,1,5 Ji-Fan Lin,3 Thomas I-Sheng Hwang1,2,6 1Division of Urology, Department of Surgery, Shin-Kong Wu Ho-Su Memorial Hospital, Taipei, Taiwan; 2Division of Urology, School of Medicine, Fu-Jen Catholic University, New Taipei, Taiwan; 3Central Laboratory, Shin-Kong Wu Ho-Su Memorial Hospital, Taipei, Taiwan; 4Department of Biotechnology, College of Health Science, Asia University, Taichung, Taiwan; 5Institute of Traditional Medicine, School of Medicine, National Yang-Ming University, Taipei, Taiwan; 6Department of Urology, Taipei Medical University, Taipei, TaiwanCorrespondence: Thomas I-Sheng HwangDivision of Urology, Department of Surgery, Shin Kong Wu Ho-Su Memorial Hospital, Taipei 11102, TaiwanTel +886-2-28332211 Ext 2065Fax +886-2-28389404Email thomashwang0828@gmail.comPo-Chun Chen Email blibra1002@gmail.comPurpose: Nuclear factor (erythroid-derived 2)-like 2, also known as NFE2L2 or NRF2, a transcription factor capable of upregulating antioxidant response element (ARE)-mediated expression and cytoprotective proteins, plays critical roles in chemoprevention, inflammation and aging. NRF2 has recently been proposed as a novel target for cancer chemoprevention. The fungicide miconazole has shown promising antiproliferative effects in cancer cells.Materials and Methods: After miconazole treatment, the p62-KEAP1-NRF2 activation was analyzed by qPCR and Western blot. The nuclear translocation indicating NRF2 activation was further confirmed by immunofluorescence. Finally, the ROS production was detected by CM-H2DCFDA staining.Results: We demonstrate in this study that miconazole dramatically increases NRF2 activation in bladder cancer cells, in a dose- and time-dependent manner. Interestingly, levels of expression of p62, a noncanonical pathway that mediates NRF2 activation, appeared to increase in accordance with NRF2. We also investigated levels of the negative regulator kelch-like ECH-associated protein 1 (KEAP1), which is involved in NRF2 activation. As expected, a decrease in KEAP1 expression was found after miconazole exposure. Confirmation of NRF2 nuclear translocation was monitored by immunofluorescence. Miconazole-induced generation of reactive oxygen species (ROS) promoted NRF2 activation. Pretreatment of bladder cancer cells with ROS scavengers abolished NRF2 expression and nuclear translocation, indicating that miconazole activates the noncanonical p62-KEAP1-NRF2 pathway, which is regulated by ROS production.Conclusion: Our study elucidates the mechanisms through which miconazole stimulates NRF2 which may contribute to cancer chemopreventive effects.Keywords: miconazole, NRF2, p62, KEAP1, bladder cancer